Emotional intelligence and caring behavior among nurses at Dr. M. Djamil General Hospital Padang - Dorisnita Dorisnita; Hartati Hartati; Melia Nuriyansyah (Institute of Computer Science (IOCS), 2026)
Emotional intelligence (EI) is crucial in nursing education to develop competencies such as communication, decision-making, and empathy. In Indonesia, 70.5% of patients perceived hospital staff as lacking empathy, and 61.4% felt consultation times were shorter compared to those abroad. The purpose of this study was to describe nurses' caring behaviors and examine their relationship with emotional intelligence. The research method used was a cross-sectional analytic study conducted on 119 nurses from various hospital units. Emotional intelligence and caring behaviors were measured using a validated questionnaire. Data were analyzed using descriptive and bivariate statistics. The results showed that most respondents were aged ≥30 years (88.2%), female (88.2%), and had a Bachelor's degree in Nursing (62.2%). More than half had high emotional intelligence (56.3%), and most demonstrated good caring behaviors (95.8%). Age, gender, and education did not significantly influence emotional intelligence or caring behaviors (p > 0.05). Emotional intelligence showed a strong and significant relationship with caring behavior (OR = 7.412; 95% CI: 3.292–16.690; p < 0.001), with a moderate positive correlation (R = 0.518). Emotional intelligence explained 26.8% of the variance in caring behavior (R² = 0.268). Emotional intelligence significantly influenced nurses' caring behavior. Nurses with higher emotional intelligence tended to provide more empathetic and compassionate care, thereby improving patient satisfaction and service quality.